Dynamic mechanical relaxation behavior of binary metallic glasses. (March 2021) - Liu, M.N.; Hao, Q.; Dong, J.; Sun, B.A.; Feng, S.D.; Crespo, D.; Qiao, J.C.
Abstract: Secondary β relaxation is a fundamental issue to understand the diffusion, plasticity and glass transition behavior of metallic glasses. Binary metallic glasses provide a simple glassy system to probe the dynamic mechanical processes. In the current research, dynamic mechanical behavior of the typical binary metallic glasses was investigated by dynamic mechanical analysis (DMA). The dynamic mechanical relaxation behavior of Cu50-x Ti50+x (x = 0, 7 and 9) and Cux Zr100-x (x = 30, 50, 56, 61.8 and 64) binary metallic glass system was studied. It is found that the β relaxation becomes pronounced with the increase of copper, which is analyzed in the framework of the principle of mixing enthalpy. However, the β relaxation of CuZr or CuTi binary metallic glasses is much more modest than that of Y65 Co35, Dy65 Co35 and Y67 Cu33 . Graphical abstract: Image 1 Highlights: Mechanical relaxation processes of binary MGs were probed by mechanical spectroscopy. β relaxation of the Cux Zr100-x binary MG systems was suspended by increasing the content of zirconium. The activation energy of the β relaxation obeys the empirical relation: Eβ 26 RT g .